Percepções dos estudantes sobre pensamento computacional e a aprendizagem de matemática - Demartini, Susana Seidel (2023)
This research aimed to answer the following question: What are the perceptions of sixth grade students in a public school about the use of Computational Thinking for learning Mathematics?. For this, a qualitative research was carried out, in which 24 students from a sixth grade class, from a municipal public school, in the metropolitan region of Porto Alegre, participated between the months of March and August 2022. They were used as data collection instruments two questionnaires, the previous one answered by the participants before carrying out the Computational Thinking activities and the post questionnaire at the end of the research. Sixteen class periods of 55 minutes each were used to carry out the activities. The research is theoretically based on authors who define and defend Constructionism and the use of Computational Thinking in education. The chosen method of analysis was Discursive Textual Analysis. From the analyzes it was possible to conclude that the students understood Computational Thinking as a way to solve problems using programming and games, to learn to think. They also associated unplugged activities with classroom activities, without the use of technology, while plugged activities were related to programming and games. Finally, for most students the Computational Thinking activities helped in learning math, especially about angles, laterality, calculations and reasoning. In addition, these activities made classes more attractive and fun.